2012 Fourth International Workshop on Quality of Multimedia Experience 2012
DOI: 10.1109/qomex.2012.6263834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mobile devices and usage location on perceived multimedia quality

Abstract: We explore the quality impact when audiovisual content is delivered to different mobile devices. Subjects were shown the same sequences on five different mobile devices and a broadcast quality television. Factors influencing quality ratings include video resolution, viewing distance, and monitor size. Analysis shows how subjects' perception of multimedia quality differs when content is viewed on different mobile devices. In addition, quality ratings from laboratory and simulated living room sessions were stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Experiments are usually performed in laboratories where videos are displayed on a TV set, but natural environments, like home or office, and different media for observing videos, like mobile devices, can be used [57,58].…”
Section: Subjective Approachmentioning
confidence: 99%
“…Experiments are usually performed in laboratories where videos are displayed on a TV set, but natural environments, like home or office, and different media for observing videos, like mobile devices, can be used [57,58].…”
Section: Subjective Approachmentioning
confidence: 99%
“…Results show that perceived quality is indeed impacted by the display device and that subjects may have higher quality expectations for devices with a larger screen. Catellier et al [19] also assessed the impact of different mobile devices, ranging from a smartphone to a laptop, on perceived multimedia quality. They found that the influence of the device and screen size has no significant influence on quality perception in the case of watching highquality video sequences.…”
Section: Overview Of Subjective Video Quality Experiments On Mobmentioning
confidence: 99%
“…The parameters of the device that affect QoE are screen resolution, screen orientation and video player. Andrew Catellier et al made an exploratory experiment [7] using five different mobile devices in two testing environments to understand how the perceived quality of video sequences differed among many devices. The mobile devices ranged from a smartphone to a 17'' laptop.…”
Section: Introductionmentioning
confidence: 99%